Confessions of a teenage drama queen - Sheldon, Dyan. (New York : Scholastics Inc., 2004)
In her first year at a suburban New Jersey high school, Mary Elizabeth Cep, who now calls herself "Lola," sets her sights on the lead in the annual drama production, and finds herself in conflict with the most popular girl in school.
G5
Keywords: Identity -- Fiction; Interpersonal relations -- Fiction; High schools -- Fiction; Schools -- Fiction